Fenomena FOMO : Bagaimana Self Control Mempengaruhi Generasi Z - Nia Bening Mutiara; Abelia Agustin; Risma Anita Puriani; Rani Mega Putri (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Fear of Missing Out or more often abbreviated as FoMO is a phenomenon that shows where an individual experiences anxiety about being left behind by trends so that it brings a lot of influence into the individual's life itself, especially Generation Z who since birth have been faced with technological advances. This study was conducted to see the picture of Self-Control's involvement in influencing Generation Z on this FoMO phenomenon. This study uses a literature study method with a narrative view design from accredited journals 5 years and under. The results of this study indicate that self-control plays a very important role in influencing Generation Z in this FoMO era.